KORELASI FILSAFAT NILAI TENTANG KEBAIKAN DENGAN AL-MASLAHAH - Harun, Muhamad; Torik, Muhammad (Nurani, 2016)
Orientation to establishment of Islamic law with a variant of the method is to achieve human welfare. To achieve the benefit of this, not just human authorized by God to made through His mind, but also God determine through His Word, so that in Islamic law, there are two sources of law, namely “naqliy” and “aqliy” always follow the development of human civilization has implications for the emergence of new problems the rule of law is not regulated in the passage, then the method “maslahah al-mursalah” into one of the alternative solutions oriented to the good of man. In other words, let alone at the level of Allah and the Massenger (via maslahah al-mu'tabarah) as a legal resident, on human writing even if the benefit to be achieved as the "fruit" of authoritative of law through “maslahah al-mursalah”. In regard to the philosophy of the value of the good, the methods of “al-maslahah” have embodied the virtues intuisisme, universalistic hedonism, utilitarianism and religiosisme.